2018
DOI: 10.3892/ijo.2018.4420
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 1 promotes the epithelial-to-mesenchymal transition in prostate cancer PC3 cells via the RAGE/NF-κB signaling pathway

Abstract: High mobility group box 1 (HMGB1), a critical damage-associated molecular pattern molecule, has been implicated in several inflammatory diseases and cancer types. The overexpression of HMGB1 protein occurs in prostate cancer, and is closely associated with the proliferation and aggressiveness of tumor cells. However, the underlying mechanisms of HMGB1-induced tumor metastasis in prostate cancer remain unclear. In the present study, it was demonstrated that the expression of HMGB1 was high in prostate cancer sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 49 publications
(65 reference statements)
0
78
0
Order By: Relevance
“…Based on previously reported results, the activation of the NF-κB signaling pathway is of primary importance for the cellular action of the RAGE receptor. 22,23,[35][36][37] We used an NF-κB reporter gene assay to confirm the functionality of this system by transfection of a pMEKK positive control, 38 and we demonstrated an increase in luciferase activity by a factor 2.38 after 45 minutes (Fig. 2C, left panel).…”
Section: Characterization Of the Rage Pathway And Its Functionality Imentioning
confidence: 85%
“…Based on previously reported results, the activation of the NF-κB signaling pathway is of primary importance for the cellular action of the RAGE receptor. 22,23,[35][36][37] We used an NF-κB reporter gene assay to confirm the functionality of this system by transfection of a pMEKK positive control, 38 and we demonstrated an increase in luciferase activity by a factor 2.38 after 45 minutes (Fig. 2C, left panel).…”
Section: Characterization Of the Rage Pathway And Its Functionality Imentioning
confidence: 85%
“…The mean serum HMGB1 level was 4.64 ng/mL in patients with malignant breast cancer, which was remarkably higher than in patients with benign breast cancer (1.32 ng/mL) or in healthy subjects (1.36 ng/mL) [75]. HMGB1 (2 µg/mL) induces EMT of colorectal and prostate cancer cells via the RAGE/NF-κB pathway [76,77]. IL-10 is a potent anti-inflammatory cytokine that suppresses T cell/macrophage cytokine synthesis and blocks their antigen-presenting capacity [78].…”
Section: Emt Inducers From Chronic Inflammatory Tumor Microenvironmentsmentioning
confidence: 83%
“…We performed IHC to identify HMGB1 expression patterns in patient tissue and explore the clinical signi cance of HMGB1 in PCa. Several researchers have reported that high HMGB1 expression was associated with pathological features, such as Gleason score, pathological stage, PSA level, and metastasis [18][19][20]. However, most of the previous studies did not analyze the expression pattern according to the stage and nuclear grade of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB signaling plays a pivotal role in cancer cell proliferation, progression, and metastasis in PCa cells [14]. An association between HMGB1 and the NF-κB signaling pathway has been widely evaluated in several solid cancers and in ammation, but rarely in PCa [15]. For this reason, we next investigated if HMGB1down-regulation could affect NF-κB signaling in prostate cancer cells using a human NF-κB proteome pro ler array.…”
Section: Suppression Of Hmgb1 Expression Inhibits the Nf-κb Pathway Imentioning
confidence: 99%